1996
DOI: 10.1002/(sici)1097-4628(19960516)60:7<1033::aid-app14>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and esterification kinetics of terephthalic acid in ethylene glycol III. The effects of functional groups

Abstract: SYNOPSISClear time (tcl), the time required for the turbid mixture of terephthalic acid (TPA) and ethylene glycol (EG) to be clear, was measured to examine the effect of poly(ethy1ene terephthalate) (PET) prepolymer (DP of 1-5) on the kinetics of dissolution and/or esterification of TPA with EG. The tcl of the mixture of TPA/EG (1 : 1.5 in molar ratio) was reduced to 1 : 2.2 or 1 : 3.5 by addition of 30 w t % of PET prepolymer or bis-(2-hydroxyl ethyl) terephthalate (BHET), respectively. Diethyl terephthalate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
2
Order By: Relevance
“…The composition of PET-G cards was determined by weighing individual components and thermogravimetric analysis (Figures S1 and S2). In the absence of an inventory database for BHET, CHDM, and DBU, the published literature , and patents were consulted for data related to the synthesis of these chemicals. The inventory data for EG, metals (scrap copper), acetone, and water were sourced from the ecoinvent database.…”
Section: Methodsmentioning
confidence: 99%
“…The composition of PET-G cards was determined by weighing individual components and thermogravimetric analysis (Figures S1 and S2). In the absence of an inventory database for BHET, CHDM, and DBU, the published literature , and patents were consulted for data related to the synthesis of these chemicals. The inventory data for EG, metals (scrap copper), acetone, and water were sourced from the ecoinvent database.…”
Section: Methodsmentioning
confidence: 99%
“…During the copolymerization, the comonomer diacid may compete with TPA for the esterication reaction with EG and may affect the dissolution and reaction kinetics, especially at higher molar contents. While detailed studies on the role of solubility in the esterication kinetics of PET have been reported, [10][11][12] to the authors' knowledge, no published study on the effect of copolymerization on the esterication step of PET synthesis is available.…”
Section: Introductionmentioning
confidence: 99%
“…A razão molar do TPA : EG e a faixa de temperatura reacional usadas são 1:1,5 -3 e 240 -260 o C, respectivamente. A utilização de uma menor razão entre os monômeros e uma maior temperatura, em comparação com o método de transesterificação, é imprescindível para alcançar uma excelente solubilidade do monômero TPA em EG [20][21][22][23][24].…”
Section: Polímerounclassified
“…Compton kα (19,20 keV) e kβ(21,56 keV); e composição), o meio passa a interagir de forma diferenciada com a radiação incidente, ocorrendo um significativo aumento da intensidade do espalhamento da fonte primária de raios-X. Além do Ródio (Rh), são observados linhas kα para: S (2,28 keV), Cl (2,62 keV), Mn (5,82 keV), Fe (6,32 keV), Cu (7,94 keV) e Sb(26,28 keV).…”
unclassified